2019
DOI: 10.1002/adfm.201903660
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Templated Conversion of Metallogel into Heterostructured TMP@Carbon Quasiaerogels Boosting Bifunctional Electrocatalysis

Abstract: Integration of nanostructured electrocatalysts into a 3D ordered assembly is beneficial for boosting their catalytic performance across various energy conversion applications. In this work, a self-templated carbonization strategy for synthesizing heterostructures of transition metal phosphide@nitrogen/phosphorus dual-doped carbon quasiaerogels (TMP@NPCA) is presented using a rationally designed precursor of a metallogel with Zn/M (M = Co, Fe, and Ni) bimetallic clusters (BMOG) and nitrogen/phosphorus chelate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 69 publications
(37 reference statements)
0
52
0
Order By: Relevance
“…It was caused by the generated gases from the pyrolysis of CTPs via a self-activation mechanism. [55] This further confirmed that heteroatom abundant CTPs can indeed be considered as ideal precursors for the preparation of metal-free carbon catalysts with abundant pores. [56] In this case, the predesigned N, P, F components in NPF-CNS-2 were fully exposed as active centers for improving ORR/OER electrocatalytic performance.…”
Section: Resultsmentioning
confidence: 54%
“…It was caused by the generated gases from the pyrolysis of CTPs via a self-activation mechanism. [55] This further confirmed that heteroatom abundant CTPs can indeed be considered as ideal precursors for the preparation of metal-free carbon catalysts with abundant pores. [56] In this case, the predesigned N, P, F components in NPF-CNS-2 were fully exposed as active centers for improving ORR/OER electrocatalytic performance.…”
Section: Resultsmentioning
confidence: 54%
“…N 1s XPS spectra for the MoS 2 ‐NCS‐2 (Figure d) can be fitted into three principal peaks of binding energies of 400.8, 398.5, and 395.4 eV, respectively, corresponding to quaternary‐N, pyrrolic‐N, and Mo 3p 3/2 , respectively 5c,26. Similar peaks are found in the MoS 2 ‐NCS‐1 and MoS 2 ‐NCS‐3 (Figure S13a,b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Transition‐metal phosphides such as Ni 2 P and CoP have been studied as substitutes for noble metal catalysts owing to their metallic characters, efficient catalytic performance, durability as well as cost‐effectiveness. [ 9–14 ] The catalytic activity of transition metal phosphide is due to a moderate interaction between phosphorus and the reaction intermediate to form a suitable surface structure as a proton acceptor site. [ 15–17 ] However, single‐phase metal phosphides suffer from an inferior catalytic performance compared with noble metal catalysts.…”
Section: Introductionmentioning
confidence: 99%